THROMBOCYTOPENIA ASSOCIATED WITH HEPATITIS B VIRUS INFECTION-CASE REPORT - Sulejmani, Haris; Bogdanovski, Nenad; Zafirova, Ivana; Krstevska Balkanov, Svetlana (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Two thirds of people with acute hepatitis B have an asymptomatic or subclinical infection that goes undetected. Progressive liver infection (counting cirrhosis and HCC) can be anticipated to develop in one quarter to one third of individuals who obtain infection within the first few years of life. While the exact mechanism underlying the correlations between HBV and various skin problems is still unknown, theories usually put up include virally related,immune-related mechanisms or direct harm brought on by viral replication. The most frequent cutaneous HBV infection symptom is acute urticaria. HBsAg positive was significantly and independently related with incidence thrombocytopenia in a large cohort research of an essentially healthy population, suggesting that mechanisms other than portal hypertension may underlie thrombocytopenia in healthy HBV carriers. We presented a case of Hepatitis B virus infection associated with thrombocytopenia.The patient was 53 years old man who was admitted in our clinic due to a maculo-papular rash predominantly in lower extremities after consuming alcohol without elevated temperature and accompanying symptoms.Lab test was performed and there were detected elevated liver enzymes and lower count of platelets.  Key words: Hepatitis B virus,Thrombocytopenia,rash